Ubiquitin Carboxyl Hydrolase L1 Significance for Human Diseases - Ngoc Anh Suong, Dang; Thi Phuong Thao, Dang; Masamitsu, Yamaguchi; Linh Thuoc, Tran (Protein and Peptide Letters, 2014)
Ubiquitin carboxyl hydrolase L1 (UCH-L1) is an abundant multifunctional neuron protein. It plays an important role in maintaining the ubiquitin proteasome system (UPS), vital for recognizing and degrading dysfunctional proteins in organisms. In recent decades, UCH-L1 has been implicated in the pathogenesis of many diseases, including neurodegenerative disorders, cancer and diabetes. However, the mechanisms of UCH-L1 involvement have yet to be revealed in detail. Since UCH-L1 contributes many different functions to cell metabolism, its role and regulation might be more complex than previously thought and it has become a research target in many laboratories. In this review, we summarize recent findings related to the actions of UCH-L1 in several human diseases.
Keywords: Parkinson’s disease